Determination of Fertilizer Doses of Plants Utilizing the Results of Aerial Photographs Using Fuzzy Tsukamoto. (March 2019) - Ubaya, Huda; Sukemi,; Oktavian, Dian
Abstract: Fertilizer dosage can be known through various methods including using digital image results. This study was taken from the results of aerial photographs with NDVI parameters, c-means and Fuzzy Tsukamoto methods which aimed to determine the dosage of fertilizer. The next step is to establish a rule base which is determined by the number of membership clusters in the c-means method and produces data that the quantity of membership cluster can determine the amount of fertilizer dose. The use of this method results in an accurate estimation of fertilizer dosage time of 97.7% compared to the conventional determination process.